Basic concepts of psychiatric-mental health nursing - Shives, Louise R.; Isaacs, Ann (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2002)
Revised to focus on the nursing model of mental health care, this handy introduction and review is the keystone to sound practice. Based on DSM-IV-TR and NANDA diagnoses with interventions presented in a nursing process context, this edition emphasizes critical concepts in continuum of care settings, client and family education, and student self-awareness. Build your knowledge base with these practical features...Multiple Choice, NCLEX-style questions assist in review and exam preparation, Self-awareness Prompts help you assess your progress, Clinical Thinking Questions and Exercises help improve clinical decision making. Inside you''ll find vital information on community and resources, client and family education, and nursing theory and research--helping define your role in the interdisciplinary team. Also new to this edition... New format highlights clnical applications and nursing-focused care-- New chapters address Cultural and Ethnic Issues, Electroconvulsive Theraphy, Alternative Therapies, Personality Disorders, Dual Diagnosis, and Persistenly Mentally Ill Clients-- Enhanced content covers psychopharmacology, abuse schizophrenia, anxiety, substance abuse, managed care, and more!
Contents: Psychiatric-Mental Health Nursing-- Components of the Nurse-Client Relationship-- Interactive Therapies-- Special Treatment Modalities-- Clients with Psychiatric Disorders-- Special Populations-- Appendices: A DSM-IV-TR Classification- Axis I and II Categories and Codes-- B. Canadian Standards of Psychiatric and Mental Health Nursing Practice-- C. Drugs Used in the Treatment of Psychiatric and Neurologic Disorders-- Internet Resources.
Includes bibliographical references and index.
Keywords: MENTAL DISORDERS -- NURSING